Coupled Electromagnetic and Thermal Analysis and Design Optimization of Synchronous Electric Machines - (:unkn) unknown (My University, 2014)
A new technique for coupling the electromagnetic, thermal, and air-flow analysis is proposed for electronically controlled synchronous machines. A computationally efficient finite element analysis (CE-FEA) technique is employed for the electromagnetic field analysis. An equivalent circuit network is used for thermal and air-flow analysis. An iterative algorithm, which exploits the fact that the type of machines studied have very low rotor losses and also a relatively reduced dependency of core losses with temperature and load, has been developed. The overall computational time is significantly reduced in comparison with the conventional coupling method, such that the new technique is highly suitable for large scale optimization studies. An automated design optimization method based on differential evolution algorithms has also been developed and implemented on a multi-core computer system. Example case studies are provided for permanent magnet and for synchronous reluctance machines. Computational and experimental results from prototype motors are included.
Keywords: Electric Machines; Electromagnetic; FEA; Optimization; Thermal Anlysis